Практико-орієнтований підхід в академічній фазі педагогічної освіти Німеччини: погляди німецьких науковців - Бобраков, Сергій (Видавництво Львівської політехніки, 2012)
В статье рассматривается структура педагогического образования в Германии, анализируются новые, бакалаврские и магистерские программы подготовки учителей, определяется процент их внедрения отдельными федеральными землями. Исследуются работы немецких ученых в направлении обеспечения профессионализации подготовки учителей, изучаются возможности практико-ориентированного подхода как способа достижения этой цели. The article reveals the structure of teacher education in Germany, analyses new Bachelor-Master teacher training programs, defines the percentage of their implementation by separate Federal States. The author analyses theses of German researchers in the area of professionalization of teacher education and studies the possibilities of practice-oriented approach as a way of this objective achievement.
Практико-ориентированный подход в академической фазе педагогического образования Германии: взгляды немецких ученых
Practice-oriented approach in academic phase of teacher education in Germany: views of German researchers
Keywords: структура педагогического образования в Германии; профессионализация университетской подготовки учителей; практико-ориентированный подход; structure of teacher education in Germany; professionalization of university teacher education; practice-oriented approach